Analisa Kasus Peran Penyuluh Swadaya Dalam Pengembangan Budidaya Minapadi di Desa Nogotirto - Purwito Zanuar Rahmadi; Ahmad Zuber; Mahendra Wijaya (Prodi Sosiologi Universitas Mataram, 2019)
The purpose of this study was to determine the role of self-help instructors in developing minapadi cultivation in Nogotirto Village. Agriculture is the main sector that still dominatesthe livelihoods of the Indonesian population. Agricultural innovation is very necessary to improve the quality and quantity of agricultural products. The results showed that Sawadaya Extension was able to provide innovative breakthroughs to provide solutions to problems that are often faced by farmers through cultivation of Minapadi. Self-helpinstructors in Latency (Maintenance Pattern) to maintain a system can run according to its structural functions. So, it has become a joint task in a working system in the SlemanMinapadi Community group and the Sleman Fishery Network Network (JMP) to maintain and maintain the patterns that are already very strong the role of self-supporting instructorsbecause it is part of the functional structural system in the group that is.